An Improved Ocean Surface Albedo Computational Scheme: Structure and Performance. Issue 8 (16th August 2021) - Wei, Jian; Ren, Tong; Yang, Ping; DiMarco, Steven F.; Mlawer, Eli
Abstract: Ocean surface albedo (OSA) is an important factor for the transfer of radiation in the coupled atmosphere‐ocean system. By resolving the spectral variations of the reflective properties for incident direct and diffuse solar radiation, we develop an OSA computational scheme to study the impact of ocean biogeochemistry on the air‐sea boundary condition of solar radiative transfer in the atmosphere. The new scheme is implemented for the General Circulation Model applications of the shortwave rapid radiative transfer model RRTMG_SW, a radiative transfer model used extensively in regional and global models. We show that a number of OSA schemes lead to underestimated results in comparison with in‐situ measurements obtained at a site 25 km east of Virginia Beach. The scheme developed in this study considers multiple influential factors and is robust in terms of the mean absolute percentage error (MAPE) and the root mean square error in comparison with in‐situ measurements. Furthermore, the new simulations are highly consistent with the Clouds and the Earth's Radiant Energy System (CERES) OSA distribution on a global scale. However, the theoretical results show slight differences compared with the CERES OSA under all sky conditions and overestimate the OSA in the subpolar Southern Ocean under clear sky conditions. The assumption of a uniform phase function, which neglects the spatial variability of the optical properties of oceanic particles, is largely responsible for the primary source of uncertainties in an OSA scheme. Plain Language Summary: Understanding the solar energy exchange between the atmosphere and the ocean is of primary importance in enhancing our ability to determine the radiative energy budget of the Earth. To describe the energy transport precisely, it is necessary to further study ocean surface albedo (OSA), the ratio of the upward radiation to the downward counterpart just above the air‐sea interface. Oversimplified OSA algorithms in climate models lead to greatly varying estimates of how changes in reflected sunlight affect the global energy balance. This study develops an improved OSA computational scheme with an appropriate treatment of the ocean surface chlorophyll concentration‐based inherent optical properties (IOPs) of the water column, which is implemented for the General Circulation Model applications of the shortwave rapid radiative transfer model RRTMG_SW. The new OSA scheme shows robust performance compared to the in‐situ measurements from the Clouds and the Earth's Radiant Energy System (CERES) Ocean Validation Experiment on a regional scale, and the CERES surface fluxes products on a global scale. This scheme is expected to reduce uncertainties in the modeling of the energy budget of the coupled atmosphere‐ocean system. Key Points: An improved ocean surface albedo (OSA) computational scheme is developed and implemented into an extensively used radiative transfer model The OSA scheme developed in this study considers multiple factors, and the computed OSA is reasonable compared to in‐situ measurements The new OSA simulations are consistent with the Clouds and the Earth's Radiant Energy System OSA distribution on a global scale